0 votes
153 views
in Uncategorized by (98.9k points)
edited by

The Boolean expression \(∼(p⇒(∼q))\) is equivalent to :

(a) p ^ q

(b)\( q⇒∼ p\)

(c) p v q

(d)  \((∼p)⇒q\)

1 Answer

0 votes
by (98.9k points)
selected by
 
Best answer

Correct option is A)  p^q 

Explaination::
\(∼(p⇒(∼q))\) 

as \({p⇒q \ is \ same \ as \ ∼p v q}\) 

we get \(∼((∼p) v(∼q)) = \)  p^q

 

Related questions

Doubtly is an online community for engineering students, offering:

  • Free viva questions PDFs
  • Previous year question papers (PYQs)
  • Academic doubt solutions
  • Expert-guided solutions

Get the pro version for free by logging in!

5.7k questions

5.1k answers

108 comments

497 users

...